Product design improvement through integration of theory of inventive problem solving (TRIZ) and design for manufacture and assembly (DFMA) - Mohamed Nazari, Munira (2010)
Theory of Inventive Problem Solving (TRIZ) is one of the Value Engineering (VE) systematic tools to improve the value of products by examination of function, by which designer can systematically solve problems and enhance decision-making. Design for Manufacture and Assembly (DFMA) is an approach to improve product performance and to simplify product. This project report describes work to integrate DFMA and TRIZ to improve and value added the current design of consumer product. The used of TRIZ concept will eliminate the contradiction problem that occurred during the process of improvement of the product by applying the principles proposed by TRIZ. TRIZ had simplified 39 standard technical characteristics that cause conflict. These are called the 39 Engineering Parameters. The conflict then can be solved by referring to the 40 Inventive Principles. Results from case studies showed that the integrating of DFMA and TRIZ can improve the product design efficiency value, minimize assembly complexity, reduce the overall assembly time and cost, and reduce the number of part in product improvement compared by just using single tool.